How fast are cross-country skiers in the finish-sprint during a sprint competition? - Haugnes, P.; Kocbach, J.; Torvik, P. Ø.; Ekren, T.; Ettema, G.; Sandbakk, O. (NVC Conference 2017, 5.-6. October 2017, Are, Sweden, 2017)
The finish-sprint of sprint cross-country (XC) skiing competitions requires high maximal speed (max) as well the ability to utilize a high fraction of Vmax at the end of a race. However, the latter ability may be influenced by skiing techniques and pacing strategy. The aim of this study was to investigate the %Vmax obtained in the finish-sprint of XC sprint competitions in classical and skating XC skiing, as well as the effect of different pacing strategies on this ability.